Black female teachers : diversifying the United States' teacher workforce - Farinde-Wu, Abiola; Allen-Handy, Ayana; Lewis, Chance W. 1972- (Emerald Publishing, 2017)
This important, timely, and provocative book explores the recruitment and retention of Black female teachers in the United States. There are over 3 million public school teachers in the US, African American teachers only comprise approximately 8 percent of the workforce. Contributions consider the implicit nuances that these teachers experience.
Keywords: Teachers, Black -- United States.; African American teachers -- United States.; Multicultural education -- United States.; United States.; elektronické knihy; electronic books